Implementation of Dijkstra's Algorithm to Find a School Shortest Distance Based on The Zoning System in South Tangerang - Sulaiman, Maulana Muhamad; Sahlan, Sahlan (Universitas Nusantara PGRI Kediri, 2022)
School is an essential thing for education quality. This time, the South Tangerang government is implementing a new student admission process using a zoning system; all prospective students must choose a school that has the shortest distance from their residence. However, many parents and prospective students do not understand this zoning system. The limited access to information is a problem for them, so they do not know where the schools are included in their zoning area. For this reason, the need to efforts the problem-solve to use Dijkstra's algorithm as a consideration to find the results more accurate for the shortest distance. So the exact solution that should implement the information technology this time is